Household Economic Management among Muslim Single-Parent Families in a Matrilineal Context - Almizan Almizan; Erizal Candra Efendi; Ruri Mustika; Indah Permata Sari; Wildan Hadi (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
This study is situated within the growing attention to non-traditional family structures and their economic dynamics, particularly in contexts where cultural norms and religious values intersect with household decision-making. It examines how Muslim single-parent families in West Sumatra manage household economics within a matrilineal cultural setting. The study aims to understand income management, expenditure prioritization, and economic coping strategies under conditions of income instability and intensive caregiving responsibilities. A qualitative case study approach is employed, drawing on in-depth interviews with single-parent household heads and analyzed through thematic analysis. The findings reveal that these households operate as active and adaptive microeconomic units. Income management commonly relies on a single primary livelihood or a limited combination of flexible informal activities. Expenditures are structured hierarchically, prioritizing basic needs, children’s education as a long-term investment, and health care as situational spending, with halal consumption serving as a guiding principle. Coping strategies include consumption control, income diversification, and reliance on extended family and social networks as informal safety nets, reinforced by the matrilineal kinship system. Economic decisions are shaped not only by rational considerations but also by internalized Islamic values such as nafkah, amanah, moderation (wasatiyyah), and perceptions of barakah. These findings highlight the importance of integrating household economics with Islamic and socio-cultural perspectives to better understand economic behavior in Muslim single-parent households and to inform more context-sensitive policy and empowerment strategies. ABSTRAK - Pengelolaan Ekonomi Rumah Tangga pada Keluarga Single-Parent Muslim dalam Konteks Budaya Matrilineal. Penelitian ini berangkat dari meningkatnya perhatian terhadap dinamika ekonomi rumah tangga dalam struktur keluarga non-tradisional, khususnya ketika nilai-nilai budaya dan agama berperan dalam membentuk pengambilan keputusan ekonomi. Studi ini bertujuan untuk menganalisis pengelolaan ekonomi rumah tangga pada keluarga single parent Muslim dalam konteks budaya matrilineal di Sumatera Barat, dengan fokus pada pengelolaan pendapatan, penentuan prioritas pengeluaran, serta strategi bertahan ekonomi di tengah ketidakstabilan pendapatan dan tingginya tanggung jawab pengasuhan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Data dikumpulkan melalui wawancara mendalam terhadap kepala rumah tangga single parent Muslim dan dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan bahwa keluarga single parent Muslim berfungsi sebagai unit ekonomi mikro yang aktif dan adaptif. Pengelolaan pendapatan umumnya bertumpu pada satu sumber nafkah utama atau kombinasi terbatas aktivitas ekonomi informal yang fleksibel. Struktur pengeluaran disusun secara hierarkis dengan memprioritaskan pemenuhan kebutuhan dasar dan pendidikan anak sebagai investasi jangka panjang, sementara pengeluaran kesehatan bersifat situasional dan konsumsi halal menjadi prinsip pengarah. Strategi bertahan ekonomi meliputi pengendalian konsumsi, diversifikasi sumber pendapatan, serta pemanfaatan dukungan keluarga besar dan jaringan sosial sebagai jaring pengaman informal yang diperkuat oleh sistem kekerabatan matrilineal. Pengambilan keputusan ekonomi tidak hanya didasarkan pada rasionalitas ekonomi, tetapi juga dipengaruhi oleh nilai-nilai Islam seperti nafkah, amanah, kesederhanaan (wasatiyyah), dan persepsi barakah. Temuan ini menegaskan pentingnya pendekatan kontekstual dan berbasis nilai dalam memahami perilaku ekonomi rumah tangga single parent Muslim serta perumusan kebijakan yang lebih responsif.